Positive electrode active material for lithium secondary battery and lithium secondary battery including the same

By coating lithium-nickel composite oxide particles with zirconium at a specific ratio, the active material addresses structural issues in lithium secondary batteries, enhancing capacity and life characteristics while improving manufacturing efficiency.

JP7604574B2Active Publication Date: 2024-12-23SAMSUNG SDI CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2023134040
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2023-06-08
Filing Date
2023-08-21
Publication Date
2024-12-23
Estimated Expiration
2043-08-21

AI Technical Summary

Technical Problem

Existing lithium secondary batteries face issues with structural collapse and cracking of positive electrode active materials, leading to reduced long-term life, increased resistance, and unsatisfactory capacity characteristics.

Method used

A positive electrode active material for lithium secondary batteries is developed, comprising secondary particles with aggregated primary particles coated with zirconium on their surfaces, where the ratio of Zr content on the single particle surface to the secondary particle surface is 1.5 to 3.0, enhancing the initial capacity, efficiency, and life characteristics.

Benefits of technology

The proposed active material improves productivity, initial capacity, and life characteristics of lithium secondary batteries by balancing the deterioration rates of different particle types, resulting in improved performance and longevity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007604574000004
    Figure 0007604574000004
  • Figure 0007604574000005
    Figure 0007604574000005
  • Figure 0007604574000006
    Figure 0007604574000006
Patent Text Reader

Abstract

To provide a positive electrode active material for a lithium secondary battery capable of improving an initial capacity, an initial efficiency, and a life characteristic of a lithium secondary battery by maximizing an efficiency of a manufacturing step of a positive electrode active material in a single particle form to improve a capacity and an efficiency of a mixed positive electrode active material, and of improving a productivity, and also provide the lithium secondary battery containing them.SOLUTION: A positive electrode active material for a lithium secondary battery, according to an embodiment, is a positive electrode active material for a lithium secondary battery, containing: a first positive electrode active material that contains a secondary particle in which a plurality of primary particles containing a lithium nickel system complex oxide is condensed and zirconium positioned onto a front surface of the secondary particle; and a second positive electrode active material that contains a single particle containing the lithium nickel system complex oxide and zirconium positioned onto the front surface of the single particle. A ratio of a content of Zr (at%) to a whole element in the front surface of the single particle of the second positive electrode active material against a content of Zr (at%) to a whole element in the front surface of the second particle of the first positive electrode active material is 1.5 to 3.0.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] The present invention relates to a positive electrode active material for a lithium secondary battery and a lithium secondary battery including the same. [Background technology]

[0002] Lithium secondary batteries, which have high energy density yet are easy to carry, are widely used as power sources for mobile information terminals such as mobile phones, laptops, and smartphones. Recently, active research has been conducted into using high-energy-density lithium secondary batteries as power sources for hybrid and electric vehicles or as power storage sources.

[0003] Various positive electrode active materials have been investigated to realize lithium secondary batteries suitable for these applications. Among these, lithium nickel oxide, lithium nickel manganese cobalt composite oxide, lithium nickel cobalt aluminum composite oxide, and lithium cobalt oxide are commonly used as positive electrode active materials. However, these positive electrode active materials suffer from structural collapse or cracking during repeated charge / discharge cycles, resulting in reduced long-term life of lithium secondary batteries and increased resistance, preventing satisfactory capacity characteristics. Therefore, there is a need for the development of new positive electrode active materials that can achieve high capacity and high energy density while maintaining long-term life characteristics. Summary of the Invention [Problem to be solved by the invention]

[0004] The efficiency of the manufacturing process of the single particle type positive electrode active material is maximized, and the capacity and efficiency of the mixed positive electrode active material are improved, thereby improving the initial capacity, initial efficiency, and life characteristics of the lithium secondary battery and increasing productivity. [Means for solving the problem]

[0005] In one embodiment, the present invention provides a positive electrode active material for a lithium secondary battery, the positive electrode active material comprising: a first positive electrode active material including secondary particles formed by agglomeration of a plurality of primary particles including a lithium-nickel-based composite oxide and zirconium located on the surfaces of the secondary particles; and a second positive electrode active material including single particles including a lithium-nickel-based composite oxide and zirconium located on the surfaces of the single particles, wherein the ratio of the Zr content (at %) relative to the total elements on the surfaces of the secondary particles of the first positive electrode active material to the Zr content (at %) relative to the total elements on the surfaces of the single particles of the second positive electrode active material is 1.5 to 3.0.

[0006] In another embodiment, a lithium secondary battery is provided that includes a positive electrode containing the positive electrode active material, a negative electrode, and an electrolyte. [Effects of the Invention]

[0007] The positive electrode active material for a lithium secondary battery manufactured according to an embodiment of the present invention has improved productivity, initial capacity, initial efficiency, and life characteristics. [Brief explanation of the drawings]

[0008] [Figure 1] 1 is a schematic diagram illustrating a lithium secondary battery according to an embodiment. [Figure 2] 1 is a SEM image of the surface of a first semi-finished positive electrode active material product prepared in Example 1. [Figure 3] 1 is a SEM image of the surface of a semi-finished product of a second positive electrode active material prepared in Example 1. [Figure 4] 1 is a graph showing the results of SEM-EDS analysis of the surfaces of the final positive electrode active materials of Example 1 and Comparative Example 1, illustrating the content (at %) of Zr relative to all elements on the surfaces of the positive electrode active materials. [Figure 5] 1 is a graph showing the results of SEM-EDS analysis of the surfaces of the final positive electrode active materials of Example 1 and Comparative Example 1, illustrating the ratio of the Zr element content (at %) to the Ni element content (at %) on the surfaces of the positive electrode active materials. [Figure 6]1 is a graph showing the results of SEM-EDS analysis of the surfaces of final positive electrode active materials in Example 1 and Comparative Example 1, illustrating the content (at %) of Zr relative to all metals excluding lithium on the surface of the positive electrode active material. [Figure 7] 1 is a graph showing the life characteristics of Example 1 and Comparative Example 1. DETAILED DESCRIPTION OF THE INVENTION

[0009] Although the present invention may be embodied in many different forms, it is not limited to the embodiments set forth herein.

[0010] The terms used herein are merely used to describe exemplary embodiments and are not intended to limit the present invention. The singular expressions include the plural expressions unless the context clearly indicates otherwise.

[0011] As used herein, "combinations thereof" refers to mixtures, laminates, composites, copolymers, alloys, blends, reaction products, and the like of compositions.

[0012] It should be understood that the terms "comprises," "comprises," or "has" are intended to specify the presence of embodied features, numbers, steps, components, or combinations thereof, but do not preclude the possible presence or addition of one or more other features, numbers, steps, components, or combinations thereof.

[0013] In the drawings, the thickness of various layers and regions is exaggerated for clarity, and similar parts are designated by the same reference numerals throughout the specification. When a layer, film, region, plate, or other part is said to be "on" or "above" another part, this includes not only the case where it is "directly on" another part, but also the case where there is another part between them. Conversely, when a part is said to be "directly on" another part, it means that there is no other part between them.

[0014] Furthermore, the term "layer" as used herein includes not only a shape formed on the entire surface when observed in a plan view, but also a shape formed on a portion of the surface.

[0015] The average particle size can be measured by methods well known to those skilled in the art, such as by using a particle size analyzer or by using a transmission electron microscope or scanning electron microscope. Alternatively, the average particle size can be calculated by measuring using a dynamic light scattering method, counting the number of particles in each particle size range, and then performing data analysis. Unless otherwise defined, the average particle size can refer to the diameter (D50) of particles whose cumulative volume is 50% by volume in the particle size distribution.

[0016] Here, "or" is not to be construed in an exclusive sense; for example, "A or B" is to be construed as including A, B, A+B, etc.

[0017] The term "metal" is understood to include general metals, transition metals and metalloids.

[0018] positive electrode active material In one embodiment, a cathode active material for a lithium secondary battery is provided, comprising: a first cathode active material including secondary particles formed by agglomerating a plurality of primary particles comprising a lithium-nickel-based composite oxide and zirconium located on the surfaces of the secondary particles; and a second cathode active material including single particles comprising a lithium-nickel-based composite oxide and zirconium located on the surfaces of the single particles. The ratio of the Zr content (at %) relative to the total elements on the surfaces of the secondary particles of the first cathode active material to the Zr content (at %) relative to the total elements on the surfaces of the single particles of the second cathode active material is 1.5 to 3.0, and may be, for example, 1.5 to 2.5 or 1.8 to 2.5. This means that in the mixed cathode active material of secondary particles and single particles, more zirconium is coated on the surfaces of the single particles, and particularly, the ratio of the Zr content (at %) relative to the Zr content (at %) on the surfaces of the single particles of the second cathode active material is 1.5 to 3.0. A positive electrode active material that satisfies these requirements will realize high capacity and energy density, while improving initial efficiency and life characteristics, and making it possible to achieve very high productivity.

[0019] The ratio of the Zr element content ratio to the Ni element content on the surface of the single particle of the second positive electrode active material to the Zr element content ratio to the Ni element content on the surface of the secondary particle of the first positive electrode active material may be 2.0 to 4.0, for example, 2.0 to 3.0, or 2.3 to 3.0.

[0020] Furthermore, the ratio of the Zr content (at %) relative to the total metal excluding lithium on the surface of the single particle of the second positive electrode active material to the Zr content (at %) relative to the total metal excluding lithium on the surface of the secondary particle of the first positive electrode active material may be 2.3 to 5.0, for example, 2.3 to 4.0, 2.3 to 3.3, or 2.6 to 3.3.

[0021] The content of Zr and other elements on the surface of the positive electrode active material may be measured through quantitative analysis using scanning electron microscope-energy dispersive X-ray spectroscopy (SEM-EDS) on the surface of the positive electrode active material. Other methods for measuring the Zr content include inductively coupled plasma mass spectrometry (ICP-MS) and inductively coupled plasma optical emission spectroscopy (ICP-OES).

[0022] The first positive electrode active material may be in the form of secondary particles formed by agglomeration of at least two or more primary particles, e.g., polycrystal, and the second positive electrode active material may be in the form of a single particle, meaning that the particle does not have a grain boundary within the particle and exists alone, or may have a monolith structure, a single structure, or non-agglomerated particles, meaning that the particles exist as an independent phase without agglomeration in the morphological phase, e.g., single crystal.

[0023] The average particle size of the secondary particles of the first positive electrode active material may be larger than the average particle size of the single particles of the second positive electrode active material. Thus, the first positive electrode active material may be expressed as large particles, large particles, or large particles, and the second positive electrode active material may be expressed as small particles, small particles, or small particles. For example, the average particle size of the secondary particles of the first positive electrode active material may be 5 μm to 25 μm, specifically 7 μm to 25 μm, 10 μm to 20 μm, or 12 μm to 18 μm. The average particle size of the single particles of the second positive electrode active material may be 1 μm to 10 μm, for example, 1 μm to 8 μm, 1 μm to 6 μm, or 2 μm to 5 μm. When the first positive electrode active material and the second positive electrode active material each satisfy the particle size range, the mixture density can be improved, resulting in high capacity and energy density. The average particle size of the first positive electrode active material may be determined by measuring the particle sizes of approximately 20 randomly selected secondary particles in a scanning electron micrograph of the positive electrode active material, and taking the diameter (D50) of the particle at 50% of the cumulative volume in the particle size distribution as the average particle size. The average particle size of the second positive electrode active material may be determined by measuring the particle sizes of approximately 20 randomly selected single particles in a scanning electron micrograph of the positive electrode active material, and taking the diameter (D50) of the particle at 50% of the cumulative volume in the particle size distribution as the average particle size.

[0024] In one embodiment, the first positive electrode active material may be included in an amount of 60 wt% to 95 wt% and the second positive electrode active material may be included in an amount of 5 wt% to 40 wt% based on the total amount of the first positive electrode active material and the second positive electrode active material. The first positive electrode active material may be included in an amount of 60 wt% to 90 wt%, or 70 wt% to 90 wt%, and the second positive electrode active material may be included in an amount of 10 wt% to 40 wt%, or 10 wt% to 30 wt%. When the content ratios of the first positive electrode active material and the second positive electrode active material are as described above, the positive electrode active material including these materials can achieve high capacity, have improved composite density, and exhibit high energy density.

[0025] The first and second positive electrode active materials may be, for example, high-nickel positive electrode active materials. For example, in a lithium-nickel composite oxide, the nickel content may be 80 mol% or more, relative to 100% by weight of the metals excluding lithium, such as 85 mol% or more, 90 mol% or more, 91 mol% or more, 99.9 mol% or less, or 99 mol% or less. Such high-nickel positive electrode active materials can achieve high capacity and high performance.

[0026] Specifically, the first positive electrode active material and the second positive electrode active material may each independently include a lithium nickel-based composite oxide represented by the following Chemical Formula 1:

[0027] [Chemical formula 1] Li a1 Ni x1 M 1 y1 M 2 z1 O 2-b1 X b1

[0028] In the above chemical formula 1, 0.9≦a1≦1.8, 0.7≦x1≦1, 0≦y1≦0.3, 0≦z1≦0.3, 0.9≦x1+y1+z1≦1.1, and 0≦b1≦0.1; M 1 and M 2 are each independently one or more elements selected from the group consisting of Al, B, Ba, Ca, Ce, Co, Cr, Cu, Fe, Mg, Mn, Mo, Nb, Si, Sr, Ti, V, W, and Zr, and X is one or more elements selected from the group consisting of F, P, and S.

[0029] In the above Chemical Formula 1, 0.8≦x1≦1, 0≦y1≦0.2, and 0≦z1≦0.2, or 0.9≦x1≦1, 0≦y1≦0.1, and 0≦z1≦0.1 may be satisfied.

[0030] For example, the first positive electrode active material and the second positive electrode active material may each independently include a lithium nickel cobalt-based composite oxide represented by the following Chemical Formula 2:

[0031] [Chemical formula 2] Li a2 Ni x2 Co y2 M 3 z2 O 2-b2 X b2

[0032] In the above chemical formula 2, 0.9≦a2≦1.8, 0.7≦x2<1, 0 <y2≦0.3、0≦z2≦0.3、0.9≦x2+y2+z2≦1.1、および0≦b2≦0.1であり、M 3 is one or more elements selected from the group consisting of Al, B, Ba, Ca, Ce, Cr, Fe, Mg, Mn, Mo, Nb, Si, Sr, Ti, V, W, and Zr, and X is one or more elements selected from the group consisting of F, P, and S.

[0033] In Chemical Formula 2, 0.8≦x2≦0.99, 0.01≦y2≦0.2, and 0.01≦z2≦0.2, or 0.9≦x2≦0.99, 0.01≦y2≦0.1, and 0.01≦z2≦0.1 may be satisfied.

[0034] For example, the first positive electrode active material and the second positive electrode active material may each independently include a lithium nickel-based composite oxide represented by the following Chemical Formula 3. The compound of Chemical Formula 3 may be lithium nickel-cobalt-aluminum oxide or lithium nickel-cobalt-manganese oxide.

[0035] [Chemical formula 3] Li a3 Ni x3 Co y3 M 4 z3 M 5 w3 O 2-b3 X b3

[0036] In the above chemical formula 3, 0.9≦a3≦1.8, 0.7≦x3≦0.98, 0.01≦y3≦0.29, 0.01≦z3≦0.29, 0≦w3≦0.29, 0.9≦x3+y3+z3+w3≦1.1, and 0≦b3≦0.1; M 4 is one or more elements selected from the group consisting of Al and Mn, 5 is one or more elements selected from the group consisting of B, Ba, Ca, Ce, Cr, Fe, Mg, Mo, Nb, Si, Sr, Ti, V, W, and Zr, and X is one or more elements selected from the group consisting of F, P, and S.

[0037] In Chemical Formula 3, 0.85≦x3≦0.98, 0.01≦y3≦0.14, 0.01≦z3≦0.14, and 0≦w3≦0.14, or 0.9≦x3≦0.98, 0.01≦y3≦0.09, 0.01≦z3≦0.09, and 0≦w3≦0.09 may be satisfied.

[0038] For example, the first and second positive electrode active materials may each independently include a cobalt-free lithium nickel-manganese oxide represented by the following Formula 4:

[0039] [Chemical formula 4] Li a4 Ni x4 Mn y4 M 6 z4 O 2-b4 X b4

[0040] In the above chemical formula 4, 0.9≦a4≦1.8, 0.7≦x4<1, 0 <y4≦0.3、0≦z4≦0.3、0.9≦x4+y4+z4≦1.1、および0≦b4≦0.1であり、M 6 is one or more elements selected from the group consisting of Al, B, Ba, Ca, Ce, Cr, Fe, Mg, Mo, Nb, Si, Sr, Ti, V, W, and Zr, and X is one or more elements selected from the group consisting of F, P, and S.

[0041] Method for producing positive electrode active material In one embodiment, a method for producing a positive electrode active material includes: (i) mixing a nickel-based composite hydroxide and a lithium raw material and performing a first heat treatment to prepare a first semi-finished positive electrode active material in the form of secondary particles in which a plurality of primary particles are aggregated; (ii) mixing a nickel-based composite hydroxide, a lithium raw material, and a zirconium raw material and performing a second heat treatment thereon, and then pulverizing the mixture to prepare a second semi-finished positive electrode active material in the form of single particles; and (iii) mixing the first semi-finished positive electrode active material and the second semi-finished positive electrode active material, mixing the zirconium raw material therein, and performing a third heat treatment thereon.

[0042] Conventionally, a method has been used in which a positive electrode active material in the form of secondary particles and a positive electrode active material in the form of single particles are mixed together and then coated with an element such as zirconium. In this case, a higher amount of zirconium is coated on the surfaces of the secondary particles than on the surfaces of the single particles. This is understood to be because the secondary particles have a higher specific surface area, a larger average particle size, and a higher weight ratio than the single particles. However, this method results in accelerated degradation of the single particles, resulting in reduced efficiency and reduced battery life. In contrast, according to one embodiment of the manufacturing method, a higher amount of zirconium is coated on the surfaces of the single particles than on the surfaces of the secondary particles. In particular, the ratio of the Zr content on the surfaces of the single particles to the Zr content on the surfaces of the secondary particles is 1.5 to 3.0. This suppresses degradation of the single particles and balances the degradation rates of the two types of particles, thereby improving battery life.

[0043] The nickel-based composite hydroxide refers to a precursor of a positive electrode active material. The first and second positive electrode active material half-finished products each contain a lithium nickel-based composite oxide and refer to the state before undergoing the final zirconium coating process. The nickel-based composite hydroxide can be represented by the following chemical formula 11. [Chemical formula 11] Ni x11 M 11 y11 M 12 z11 (OH)2 In the formula 11, 0.9≦a11≦1.8, 0.7≦x11≦1, 0≦y11≦0.3, 0≦z11≦0.3, 0.9≦x11+y11+z11≦1.1, and 0≦b11≦0.1; M 11 and M 12 are each independently one or more elements selected from the group consisting of Al, B, Ba, Ca, Ce, Co, Cr, Cu, Fe, Mg, Mn, Mo, Nb, Si, Sr, Ti, V, W, and Zr. In the step of producing the first semi-finished cathode active material, the first heat treatment may be performed at about 600°C to 850°C, for example, 650°C to 800°C or 700°C to 780°C, for about 5 hours to 12 hours, for example, 6 hours to 10 hours. The first heat treatment temperature may be the same as or lower than the second heat treatment temperature, and the first heat treatment time may be the same as or longer than the second heat treatment time.

[0044] In the step of preparing the second semi-finished cathode active material, the second heat treatment may be performed at approximately 650°C to 850°C, for example, 700°C to 820°C or 750°C to 800°C. The second heat treatment may be performed for approximately 5 to 12 hours, for example, 6 to 10 hours. Generally, the preparation of single particles requires firing at a high temperature of 900°C or higher, which requires a long firing period of 12 hours or more. On the other hand, in one embodiment, the use of a zirconium raw material in the preparation of single particles allows firing at a relatively low temperature and shortens the firing time. This significantly increases the weight of single particles that can be produced per day, thereby increasing productivity by approximately 10 times. Furthermore, in the case of conventional high-temperature firing, it is difficult to crush the particles due to over-sintering, making it difficult to control the particle shape. However, in one embodiment, firing at a low temperature for a short time facilitates particle crushing, which is advantageous for the particle size reduction process and simplifies the particle shape control, which is a key characteristic of single particles. In the step of producing the second positive electrode active material semi-finished product, the content of zirconium in the zirconium raw material may be 0.1 to 5 molar parts, 0.1 to 3 molar parts, 0.1 to 1 molar part, or 0.1 to 0.5 molar parts relative to 100 parts by weight of the metal in the nickel-based composite hydroxide.

[0045] The first and second positive electrode active material semi-finished products may be mixed in a weight ratio of 95:5 to 60:40, for example, 90:10 to 60:40 or 80:20 to 60:40, which can maximize the mixture density and increase the capacity.

[0046] The process of mixing the first and second semi-finished positive electrode active material products can include, for example, washing the mixture in a solvent such as distilled water, followed by drying. A zirconium raw material may be added to the dried mixture, followed by a third heat treatment in a dry furnace. The zirconium raw material may be added in an amount of 0.1 to 5 molar parts, 0.1 to 3 molar parts, 0.1 to 1 molar parts, or 0.1 to 0.5 molar parts of zirconium per 100 molar parts of all metals in the mixture excluding lithium.

[0047] The third heat treatment can be carried out at, for example, 500° C. to 800° C., or 650° C. to 750° C., for 4 hours to 24 hours, or 10 hours to 20 hours.

[0048] Lithium secondary battery Another embodiment provides a lithium secondary battery including a positive electrode, a negative electrode, a separator positioned between the positive electrode and the negative electrode, and an electrolyte.

[0049] 1 is a schematic diagram illustrating a lithium secondary battery according to one embodiment. Referring to FIG. 1, the lithium secondary battery 100 according to one embodiment includes a battery cell including a positive electrode 114, a negative electrode 112 facing the positive electrode 114, a separator 113 disposed between the positive electrode 114 and the negative electrode 112, and a lithium secondary battery electrolyte impregnated in the positive electrode 114, the negative electrode 112, and the separator 113, a battery container 120 housing the battery cell, and a sealing member 140 sealing the battery container 120.

[0050] positive electrode A positive electrode for a lithium secondary battery may include a current collector and a positive electrode active material layer disposed on the current collector. The positive electrode active material layer includes a positive electrode active material and may further include a binder and / or a conductive material.

[0051] The binder serves to firmly adhere the positive electrode active material particles to each other and to firmly adhere the positive electrode active material to the current collector. Representative examples of the binder include, but are not limited to, polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, polymers containing ethylene oxide, polyvinylpyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylated styrene-butadiene rubber, epoxy resin, and nylon.

[0052] The content of the binder in the positive electrode active material layer may be approximately 1 wt % to 5 wt % based on the total weight of the positive electrode active material layer.

[0053] The conductive material is used to impart conductivity to the electrodes, and any material that does not cause a chemical change in the constructed battery and is electron-conductive can be used. Examples of the conductive material include carbon-based materials such as natural graphite, artificial graphite, carbon black, acetylene black, ketjen black, carbon fiber, carbon nanofiber, and carbon nanotube; metal-based materials in the form of metal powder or metal fiber containing copper, nickel, aluminum, silver, etc.; conductive polymers such as polyphenylene derivatives; and conductive materials containing mixtures thereof.

[0054] The content of the conductive material in the positive electrode active material layer may be 1 wt % to 5 wt % based on the total weight of the positive electrode active material layer.

[0055] The positive electrode current collector may be, but is not limited to, aluminum foil.

[0056] negative electrode A negative electrode for a lithium secondary battery includes a current collector and a negative electrode active material layer disposed on the current collector. The negative electrode active material layer includes a negative electrode active material and may further include a binder and / or a conductive material.

[0057] The negative electrode active material includes a material capable of reversibly intercalating / deintercalating lithium ions, lithium metal, a lithium metal alloy, a material capable of being doped with and dedoped from lithium, or a transition metal oxide.

[0058] The material capable of reversibly intercalating / deintercalating lithium ions may be a carbon-based negative electrode active material, such as crystalline carbon, amorphous carbon, or a combination thereof. Examples of the crystalline carbon include graphite such as amorphous, plate-like, flake-like, spherical, or fibrous natural graphite or artificial graphite, and examples of the amorphous carbon include soft carbon, hard carbon, mesophase pitch carbide, and calcined coke.

[0059] As the lithium metal alloy, an alloy of lithium and a metal selected from the group consisting of Na, K, Rb, Cs, Fr, Be, Mg, Ca, Sr, Si, Sb, Pb, In, Zn, Ba, Ra, Ge, Al, and Sn can be used.

[0060] The material capable of doping and dedoping lithium may be a Si-based negative electrode active material or a Sn-based negative electrode active material. Examples of the Si-based negative electrode active material include silicon, silicon-carbon composites, and SiO x(0 < x < 2), Si-Q alloy (where Q is an element selected from the group consisting of an alkali metal, an alkaline earth metal, a Group 13 element, a Group 14 element, a Group 15 element, a Group 16 element, a transition metal, a rare earth element, and combinations thereof, and is not Si), examples of the Sn-based negative electrode active material include Sn, SnO2, Sn-R alloy (where R is an element selected from the group consisting of an alkali metal, an alkaline earth metal, a Group 13 element, a Group 14 element, a Group 15 element, a Group 16 element, a transition metal, a rare earth element, and combinations thereof, and is not Sn), etc., and at least one of these can also be used by mixing with SiO2. As the elements Q and R, Mg, Ca, Sr, Ba, Ra, Sc, Y, Ti, Zr, Hf, Rf, V, Nb, Ta, Db, Cr, Mo, W, Sg, Tc, Re, Bh, Fe, Pb, Ru, Os, Hs, Rh, Ir, Pd, Pt, Cu, Ag, Au, Zn, Cd, B, Al, Ga, Sn, In, Tl, Ge, P, As, Sb, Bi, S, Se, Te, Po, and those selected from the group consisting of combinations thereof can be used.

[0061] The silicon-carbon composite may include, for example, a silicon-carbon composite including a core containing crystalline carbon and silicon particles, and an amorphous carbon coating layer disposed on the core surface. The crystalline carbon may be artificial graphite, natural graphite, or a combination thereof. The amorphous carbon precursor may be coal-based pitch, mesophase pitch, petroleum-based pitch, coal-based oil, petroleum-based heavy oil, or a polymer resin such as phenolic resin, furan resin, or polyimide resin. The silicon content may be 10 wt% to 50 wt% of the total weight of the silicon-carbon composite. The crystalline carbon content may be 10 wt% to 70 wt% of the total weight of the silicon-carbon composite, and the amorphous carbon content may be 20 wt% to 40 wt% of the total weight of the silicon-carbon composite. The amorphous carbon coating layer may have a thickness of 5 nm to 100 nm. The silicon particles may have an average particle size (D50) of 10 nm to 20 μm. The silicon particles may have an average particle size (D50) of preferably 10 nm to 200 nm. The silicon particles are present in an oxidized state, and at this time, the atomic ratio of Si:O in the silicon particles, which indicates the degree of oxidation, may be 99:1 to 33:67. x In this case, SiO x In this specification, x may be in the range of more than 0 and less than 2. Unless otherwise defined, the average particle size (D50) refers to the diameter of particles whose cumulative volume is 50% by volume in the particle size distribution.

[0062] The Si-based or Sn-based negative electrode active material can be mixed with a carbon-based negative electrode active material, and when the Si-based or Sn-based negative electrode active material and the carbon-based negative electrode active material are mixed, the mixing ratio by weight may be 1:99 to 90:10.

[0063] The content of the negative electrode active material in the negative electrode active material layer may be 95 wt % to 99 wt % based on the total weight of the negative electrode active material layer.

[0064] In one embodiment, the negative electrode active material layer may further include a binder and, optionally, a conductive material. The content of the binder in the negative electrode active material layer may be 1 wt% to 5 wt% based on the total weight of the negative electrode active material layer. When the conductive material is further included, the negative electrode active material layer may include 90 wt% to 98 wt% of the negative electrode active material, 1 wt% to 5 wt% of the binder, and 1 wt% to 5 wt% of the conductive material.

[0065] The binder serves to firmly adhere the negative active material particles to each other and to the current collector, and may be a water-insoluble binder, a water-soluble binder, or a combination thereof.

[0066] Examples of the water-insoluble binder include polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, polymers containing ethylene oxide, ethylene propylene copolymers, polystyrene, polyvinylpyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, polyamideimide, polyimide, and combinations thereof.

[0067] The water-soluble binder may be a rubber-based binder or a polymer resin binder. The rubber-based binder may be selected from styrene butadiene rubber, acrylated styrene butadiene rubber, acrylonitrile-butadiene rubber, acrylic rubber, butyl rubber, fluororubber, and combinations thereof. The polymer resin binder may be selected from polyethylene oxide, polyvinylpyrrolidone, polyepichlorohydrin, polyphosphazene, polyacrylonitrile, ethylene propylene diene copolymer, polyvinylpyridine, chlorosulfonated polyethylene, latex, polyester resin, acrylic resin, phenolic resin, epoxy resin, polyvinyl alcohol, and combinations thereof.

[0068] When a water-soluble binder is used as the negative electrode binder, a cellulose-based compound capable of imparting viscosity may be further included. The cellulose-based compound may be a mixture of one or more of carboxymethyl cellulose, hydroxypropyl methyl cellulose, methyl cellulose, or alkali metal salts thereof. The alkali metal may be Na, K, or Li. The amount of the thickener used may be 0.1 to 3 parts by weight per 100 parts by weight of the negative electrode active material.

[0069] The conductive material is used to impart conductivity to the electrode, and any material that does not cause a chemical change in the constructed battery and is electron-conductive can be used. Examples of conductive materials that can be used include carbon-based materials such as natural graphite, artificial graphite, carbon black, acetylene black, ketjen black, carbon fiber, carbon nanofiber, and carbon nanotube; metal-based materials in the form of metal powder or metal fiber, including copper, nickel, aluminum, and silver; conductive polymers such as polyphenylene derivatives; and conductive materials including mixtures thereof.

[0070] The negative electrode current collector may be selected from the group consisting of copper foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam, a polymer substrate coated with a conductive metal, and combinations thereof.

[0071] electrolyte The electrolyte includes a non-aqueous organic solvent and a lithium salt.

[0072] The non-aqueous organic solvent serves as a medium through which ions involved in the electrochemical reaction of the battery can migrate. Examples of the non-aqueous organic solvent include carbonates, esters, ethers, ketones, alcohols, and aprotic solvents. Examples of carbonate solvents include dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), methyl ethyl carbonate (MEC), ethylene carbonate (EC), propylene carbonate (PC), and butylene carbonate (BC). Examples of the ester solvent include methyl acetate, ethyl acetate, n-propyl acetate, dimethyl acetate, methyl propionate, ethyl propionate, γ-butyrolactone, decanolide, valerolactone, mevalonolactone, caprolactone, etc. Examples of the ether solvent include dibutyl ether, tetraglyme, diglyme, dimethoxyethane, 2-methyltetrahydrofuran, tetrahydrofuran, etc. Examples of the ketone solvent include cyclohexanone, etc. In addition, examples of the alcohol solvent that can be used include ethyl alcohol and isopropyl alcohol, and examples of the aprotic solvent that can be used include nitriles such as R-CN (where R is a hydrocarbon group having 2 to 20 carbon atoms and having a linear, branched, or cyclic structure, and may contain a double bond, an aromatic ring, or an ether bond), amides such as dimethylformamide, dioxolanes such as 1,3-dioxolane, and sulfolanes.

[0073] The non-aqueous organic solvents may be used alone or in combination of two or more thereof. When two or more thereof are used in combination, the mixing ratio may be appropriately adjusted depending on the desired battery performance, which should be widely understood by those skilled in the art.

[0074] In addition, in the case of the carbonate-based solvent, a cyclic carbonate and a chain carbonate can be mixed and used. In this case, the performance of the electrolyte is excellent when the cyclic carbonate and the chain carbonate are mixed in a volume ratio of about 1:1 to about 1:9.

[0075] The non-aqueous organic solvent may further include an aromatic hydrocarbon-based organic solvent in addition to the carbonate-based solvent, and the carbonate-based solvent and the aromatic hydrocarbon-based organic solvent may be mixed in a volume ratio of about 1:1 to about 30:1.

[0076] The aromatic hydrocarbon solvent may be an aromatic hydrocarbon compound represented by the following formula I:

[0077] [ka]

[0078] In the above chemical formula I, R 4 ~R 9 are the same or different and are selected from the group consisting of hydrogen, halogen, alkyl groups having 1 to 10 carbon atoms, haloalkyl groups having 1 to 10 carbon atoms, and combinations thereof.

[0079] Specific examples of the aromatic hydrocarbon solvent include benzene, fluorobenzene, 1,2-difluorobenzene, 1,3-difluorobenzene, 1,4-difluorobenzene, 1,2,3-trifluorobenzene, 1,2,4-trifluorobenzene, chlorobenzene, 1,2-dichlorobenzene, 1,3-dichlorobenzene, 1,4-dichlorobenzene, 1,2,3-trichlorobenzene, 1,2,4-trichlorobenzene, iodobenzene, 1,2-diiodobenzene, 1,3-diiodobenzene, 1,4-diiodobenzene, 1,2,3-triiodobenzene, 1,2,4-triiodobenzene, toluene, fluorobenzene, fluoroisopropyl ether ... and combinations thereof.

[0080] The electrolyte may further include vinylene carbonate or an ethylene carbonate-based compound of the following formula II as a life-enhancing additive to improve battery life.

[0081] [ka]

[0082] In the above chemical formula II, R 10 and R 11 are the same or different and are selected from the group consisting of hydrogen, a halogen group, a cyano group, a nitro group, and a fluorinated alkyl group having 1 to 5 carbon atoms; 10 and R 11At least one of R is selected from the group consisting of a halogen group, a cyano group, a nitro group, and a fluorinated alkyl group having 1 to 5 carbon atoms, with the proviso that R 10 and R 11 But it's not all hydrogen.

[0083] Representative examples of the ethylene carbonate-based compound include difluoroethylene carbonate, chloroethylene carbonate, dichloroethylene carbonate, bromoethylene carbonate, dibromoethylene carbonate, nitroethylene carbonate, cyanoethylene carbonate, fluoroethylene carbonate, etc. When such a life-improving additive is further used, the amount used can be appropriately adjusted.

[0084] The lithium salt is dissolved in a non-aqueous organic solvent and serves as a source of lithium ions in the battery, enabling basic operation of a lithium secondary battery, and promoting the movement of lithium ions between the positive electrode and the negative electrode.

[0085] Representative examples of lithium salts include LiPF6, LiBF4, LiSbF6, LiAsF6, LiN(SO2C2F5)2, Li(CF3SO2)2N, LiN(SO3C2F5)2, Li(FSO2)2N (lithium bis(fluorosulfonyl)imide; LiFSI), LiC4F9SO3, LiClO4, LiAlO2, LiAlCl4, LiPO2F2, and LiN(C x F 2x+1 SO2)(C y F 2y+1SO2) (where x and y are natural numbers, for example, integers of 1 to 20), lithium difluoro(bisoxalato)phosphate, LiCl, LiI, LiB(C2O4)2 (lithium bis(oxalato)borate; LiBOB), and lithium difluoro(oxalato)borate (LiDFOB).

[0086] The lithium salt concentration is preferably within the range of 0.1 M to 2.0 M. When the lithium salt concentration is within this range, the electrolyte has appropriate conductivity and viscosity, thereby exhibiting excellent electrolyte performance and allowing lithium ions to migrate effectively.

[0087] The separator 113 separates the positive electrode 114 and the negative electrode 112 and provides a path for lithium ions to move. Any separator commonly used in lithium ion batteries can be used. That is, a separator with low resistance to electrolyte ion movement and excellent electrolyte humidification capability can be used. For example, the separator 113 can include glass fiber, polyester, polyethylene, polypropylene, polytetrafluoroethylene, or a combination thereof, and can be in the form of a nonwoven or woven fabric. For example, polyolefin-based polymer separators such as polyethylene and polypropylene are commonly used in lithium ion batteries. Coated separators containing ceramic components or polymer materials can also be used to ensure heat resistance or mechanical strength, and can be used in either a single-layer or multi-layer structure.

[0088] Lithium secondary batteries can be classified into lithium ion batteries, lithium ion polymer batteries, and lithium polymer batteries depending on the type of separator and electrolyte used, into cylindrical, prismatic, coin, pouch, etc. depending on the shape, and into bulk and thin film types depending on the size. The structure and manufacturing method of these batteries are widely known in this field, so a detailed description will be omitted.

[0089] The lithium secondary battery according to an embodiment achieves high capacity and has excellent storage stability, life characteristics, and high rate characteristics at high temperatures, and can be used in electric vehicles (EVs), hybrid vehicles such as plug-in hybrid electric vehicles (PHEVs), and portable electronic devices.

[0090] Examples of the present invention and comparative examples are described below. The following examples are merely examples of the present invention, and the present invention is not limited to the following examples. [Example]

[0091] Example 1 1. First positive electrode active material semi-finished product manufacturing The metal raw materials, nickel sulfate, cobalt sulfate, and manganese sulfate, are dissolved in distilled water as a solvent in a molar ratio of 95:4:1 to prepare a mixed metal raw material solution, and ammonia water (NH4OH) and sodium hydroxide (NaOH) as a precipitant are prepared to form a complex compound. After the diluted ammonia water is added to the continuous reactor, the mixed metal raw material solution is continuously added, and sodium hydroxide is added to maintain the pH inside the reactor. The reaction is carried out gradually for approximately 80 hours, and once the reaction has stabilized, the overflowing product is collected, washed, and dried to obtain secondary particle-form nickel-based composite hydroxide (Ni 0.95 Co 0.04 Mn 0.01 (OH)2).

[0092] The resulting nickel-based composite hydroxide and LiOH satisfying Li / (Ni+Co+Mn)=1.05 were placed in a calcination furnace and heat-treated in an oxygen atmosphere at 750°C for 15 hours to produce a lithium nickel-based composite oxide in the form of secondary particles formed by aggregation of primary particles, with the average particle size of the secondary particles being approximately 15µm. Figure 2 is an SEM image of the surface of the secondary particles, which are the first cathode active material semi-finished product.

[0093] 2. Manufacturing of second positive electrode active material semi-finished products The metal raw materials, nickel sulfate, cobalt sulfate, and manganese sulfate, are dissolved in distilled water as a solvent in a molar ratio of 95:4:1 to prepare a mixed metal raw material solution, and a diluted ammonia water (NH4OH) solution and sodium hydroxide (NaOH) are prepared as a precipitant to form a complex compound. The mixed metal raw material solution, ammonia water, and sodium hydroxide are added to the reactor while controlling the pH to decrease at the same rate, and the reaction is carried out for approximately 20 hours while stirring. The slurry solution in the reactor is filtered and washed with high-purity distilled water, and then dried for 24 hours to obtain nickel-based composite hydroxide (Ni 0.95 Co 0.04 Mn 0.01 (OH)2) powder was obtained.

[0094] The resulting nickel-based composite hydroxide was mixed with LiOH satisfying the Li / (Ni+Co+Mn)=1.05 ratio and ZrO2 so that Zr was 0.2 molar parts per 100 molar parts of the total metals in the nickel-based composite hydroxide (excluding lithium). The mixture was then placed in a calcination furnace and heat-treated at 800°C for 8 hours in an oxygen atmosphere. The resulting material was pulverized to produce single-particle lithium-nickel-based composite oxide with an average particle size of approximately 2.7 μm. Figure 3 shows an SEM image of the single-particle second cathode active material semi-finished product.

[0095] 3. Preparation of final cathode active material The first and second semi-finished cathode active materials were placed in a distilled water solvent in a weight ratio of 70:30, washed, and then dried. The resulting material and ZrO2 were placed in a firing furnace so that Zr was 0.25 moles per 100 moles of the total metals in the resulting material (excluding lithium), and heat-treated in an oxygen atmosphere at approximately 710°C for 15 hours to produce the final cathode active material.

[0096] 4. Fabrication of the Positive Electrode A positive electrode active material slurry was prepared by mixing 95% by weight of the final positive electrode active material, 3% by weight of polyvinylidene fluoride binder, and 2% by weight of carbon nanotube conductive material in N-methylpyrrolidone solvent. The positive electrode active material slurry was applied to an aluminum current collector, dried, and then rolled to prepare a positive electrode.

[0097] 5. Lithium secondary battery manufacturing A coin half-cell is fabricated using the prepared positive electrode and lithium metal counter electrode, with a polyethylene-polypropylene multilayer separator between them, and an electrolyte solution of 1.0 M LiPF6 lithium salt added to a solvent of ethylene carbonate and diethyl carbonate mixed in a 50:50 volume ratio.

[0098] Comparative Example 1 A cathode active material was prepared and a lithium secondary battery was manufactured in substantially the same manner as in Example 1, except that ZrO was not added during the heat treatment in "2. Preparation of second cathode active material semi-finished product" of Example 1 and the heat treatment was performed at 900°C for 14 hours.

[0099] Evaluation example 1: Zr content analysis on the surface of the positive electrode active material (SEM-EDS) First, a TOF-SIMS analysis was performed on a cross section of the final positive electrode active material produced in Example 1. As a result, Zr was not detected inside the first positive electrode active material and the second positive electrode active material, and it was confirmed that Zr did not enter the lattice of the lithium nickel-based composite oxide.

[0100] Next, SEM-EDS analysis was performed on the surfaces of the final cathode active materials prepared in Example 1 and Comparative Example 1 to measure the Zr content on the surface of the first cathode active material in the form of secondary particles and the Zr content on the surface of the second cathode active material in the form of single particles, respectively. The results are shown in FIGS. 4 to 6.

[0101] FIG. 4 shows the Zr content (at %) relative to all elements on the surface of the positive electrode active material, FIG. 5 shows the ratio of the Zr content (at %) relative to the Ni content (at %) on the surface of the positive electrode active material, and FIG. 6 shows the Zr content (at %) relative to all metals excluding lithium on the surface of the positive electrode active material.

[0102] 4, the average Zr content relative to all elements in the first positive electrode active material of Example 1 was approximately 0.38 at%, and the average Zr content relative to all elements in the second positive electrode active material of Example 1 was approximately 0.68 at%, resulting in a calculated ratio of approximately 1.8. Also, the average Zr content relative to all elements in the first positive electrode active material of Comparative Example 1 was approximately 0.42 at%, and the average Zr content relative to all elements in the second positive electrode active material of Comparative Example 1 was approximately 0.24 at%, resulting in a calculated ratio of approximately 0.6.

[0103] 5, the average ratio of the Zr content to the Ni content in the first positive electrode active material of Example 1 was approximately 0.021, and the average ratio of the Zr content to the Ni content in the second positive electrode active material of Example 1 was approximately 0.049, resulting in a calculated ratio of approximately 2.3. Also, the average ratio of the Zr content to the Ni content in the first positive electrode active material of Comparative Example 1 was approximately 0.024, and the average ratio of the Zr content to the Ni content in the second positive electrode active material of Comparative Example 1 was approximately 0.015, resulting in a calculated ratio of approximately 0.6.

[0104] 6, the average Zr content relative to (Ni+Co+Al+Mn+Zr) in the first positive electrode active material of Example 1 was approximately 1.06 at%, and the average Zr content relative to (Ni+Co+Al+Mn+Zr) in the second positive electrode active material of Example 1 was approximately 2.77 at%, resulting in a calculated ratio of approximately 2.6. Also, the average Zr content relative to (Ni+Co+Al+Mn+Zr) in the first positive electrode active material of Comparative Example 1 was approximately 1.20 at%, and the average Zr content relative to (Ni+Co+Al+Mn+Zr) in the second positive electrode active material of Comparative Example 1 was approximately 0.86 at%, resulting in a calculated ratio of approximately 0.7.

[0105] The following Table 1 briefly shows the analysis results of Figures 4 to 6. In Table 1, small particles refer to the second positive electrode active material, and large particles refer to the first positive electrode active material.

[0106] [Table 1]

[0107] When Zr coating is performed after mixing the first positive electrode active material in the form of secondary particles and the second positive electrode active material in the form of single particles, as in Comparative Example 1, more Zr is present in the first positive electrode active material than in the second positive electrode active material. This is understood to be because the first positive electrode active material is heavier in weight and has a larger particle size than the second positive electrode active material. On the other hand, when Zr raw material is added in the step of preparing the second positive electrode active material, and then the first and second positive electrode active materials are mixed and Zr coating is performed, as in Example 1, it is confirmed that more Zr is present in the second positive electrode active material than in the first positive electrode active material.

[0108] In Example 1, the use of Zr as a raw material in the preparation of the single-particle second cathode active material enabled firing at a lower temperature and shortened firing time, resulting in an approximately 10-fold increase in productivity. It was also confirmed that the process of grinding to obtain the single-particle form was easier, providing advantageous control of particle shape. Furthermore, when a mixed cathode active material in the form of a second cathode active material coated with more Zr is applied in this manner, the initial charge / discharge capacity, initial efficiency, and lifespan characteristics of a lithium secondary battery are improved.

[0109] Evaluation example 2: Performance evaluation of lithium secondary batteries The lithium secondary batteries prepared in Example 1 and Comparative Example 1 were initially charged at a constant current (0.2 C) and constant voltage (4.25 V, 0.05 C cutoff), rested for 10 minutes, and then discharged to 3.0 V under a constant current (0.2 C) condition. Subsequently, they were charged and discharged 150 times at 0.5 C / 0.5 C at 45°C. The capacity retention, which is the ratio of the discharge capacity at each cycle to the initial discharge capacity, i.e., the high-temperature life characteristics, were evaluated, and the results are shown in Figure 7.

[0110] Referring to FIG. 7, it can be seen that Example 1 has improved life characteristics compared to Comparative Example 1.

[0111] Although the preferred embodiments have been described in detail above, the scope of the present invention is not limited thereto, and various modifications and improvements made by those skilled in the art using the basic concepts defined in the following claims also fall within the scope of the present invention. [Explanation of symbols]

[0112] 100: Lithium secondary battery 112: Negative electrode 113: Separator 114: Positive electrode 120:Battery container 140: Sealing member

Claims

1. a first positive electrode active material including: secondary particles formed by agglomerating a plurality of primary particles including a lithium nickel-based composite oxide; and zirconium located on surfaces of the secondary particles; and A positive electrode active material for a lithium secondary battery, comprising: a single particle including a lithium nickel-based composite oxide; and a second positive electrode active material including zirconium located on a surface of the single particle, a ratio of a Zr content (at %) relative to all elements on the surface of the secondary particle of the first positive electrode active material to a Zr content (at %) relative to all elements on the surface of the single particle of the second positive electrode active material is 1.5 to 3.

0.

2. 2. The positive electrode active material for a lithium secondary battery according to claim 1, wherein a ratio of a Zr content (at %) with respect to all elements on a surface of the single particle of the second positive electrode active material to a Zr content (at %) with respect to all elements on a surface of the secondary particle of the first positive electrode active material is 1.8 to 2.

5.

3. 2. The positive electrode active material for lithium secondary batteries according to claim 1, wherein a ratio of a Zr element content ratio to a Ni element content on a surface of the secondary particle of the first positive electrode active material to a Zr element content ratio to a Ni element content on a surface of the single particle of the second positive electrode active material is 2.0 to 4.

0.

4. 2. The positive electrode active material for lithium secondary batteries according to claim 1, wherein a ratio of a Zr element content ratio to a Ni element content on a surface of the secondary particle of the first positive electrode active material to a Zr element content ratio to a Ni element content on a surface of the single particle of the second positive electrode active material is 2.0 to 3.

0.

5. 2. The positive electrode active material for a lithium secondary battery according to claim 1, wherein a ratio of a content (at %) of Zr relative to the total metal excluding lithium on the surface of the secondary particle of the first positive electrode active material to a content (at %) of Zr relative to the total metal excluding lithium on the surface of the single particle of the second positive electrode active material is 2.3 to 5.

0.

6. 2. The positive electrode active material for a lithium secondary battery according to claim 1, wherein a ratio of a Zr content (at %) relative to the total metal excluding lithium on the surface of the secondary particle of the first positive electrode active material to a Zr content (at %) relative to the total metal excluding lithium on the surface of the single particle of the second positive electrode active material is 2.6 to 3.

3.

7. 2 . The positive electrode active material for a lithium secondary battery according to claim 1 , wherein an average particle size of the secondary particles of the first positive electrode active material is larger than an average particle size of the single particle of the second positive electrode active material.

8. The average particle size of the secondary particles of the first positive electrode active material is 5 μm to 25 μm; 2. The positive electrode active material for a lithium secondary battery according to claim 1, wherein the average particle size of the single particle of the second positive electrode active material is 1 μm to 10 μm.

9. 2. The positive electrode active material for a lithium secondary battery according to claim 1, wherein the first positive electrode active material is contained in an amount of 60% by weight to 95% by weight, and the second positive electrode active material is contained in an amount of 5% by weight to 40% by weight, based on the total amount of the first positive electrode active material and the second positive electrode active material.

10. The positive electrode active material for a lithium secondary battery according to claim 1, wherein the lithium nickel-based composite oxide of the first positive electrode active material and the lithium nickel-based composite oxide of the second positive electrode active material are each independently represented by the following chemical formula 1: [Chemical formula 1] Li a1 Ni x1 M 1 y1 M 2 z1 O 2-b1 X b1 In the above chemical formula 1, 0.9≦a1≦1.2, 0.7≦x1≦1, 0≦y1≦0.3, 0≦z1≦0.3, 0.9≦x1+y1+z1≦1.1, and 0≦b1≦0.1; M 1 and M. 2 are each independently one or more elements selected from the group consisting of Al, B, Ba, Ca, Ce, Co, Cr, Cu, Fe, Mg, Mn, Mo, Nb, Si, Sr, Ti, V, W, and Zr, and X is one or more elements selected from the group consisting of F, P, and S.

11. A nickel-based composite hydroxide and a lithium raw material are mixed and subjected to a first heat treatment to prepare a first semi-finished product of a positive electrode active material having a secondary particle form in which a plurality of primary particles are aggregated; a nickel-based composite hydroxide, a lithium raw material, and a zirconium raw material are mixed and subjected to a second heat treatment, and then pulverized to prepare a second positive electrode active material semi-finished product in the form of a single particle; A method for producing a positive electrode active material, comprising: mixing a first semi-finished positive electrode active material and a second semi-finished positive electrode active material; mixing the mixture with a zirconium raw material; and subjecting the mixture to a third heat treatment.

12. The method for producing a positive electrode active material according to claim 11, wherein the second heat treatment is performed at 650°C to 850°C.

13. 12. The method of claim 11, wherein in the step of preparing the second semi-finished positive electrode active material, the zirconium content of the zirconium raw material is 0.1 to 5 parts by weight based on 100 parts by weight of the metal of the nickel-based composite hydroxide.

14. The method for producing a positive electrode active material according to claim 11, wherein the first positive electrode active material semi-finished product and the second positive electrode active material semi-finished product are mixed in a weight ratio of 95:5 to 60:

40.

15. The method for producing a positive electrode active material according to claim 11, wherein the third heat treatment is carried out at a temperature in the range of 500°C to 800°C.

16. 12. The method of claim 11, wherein a content of zirconium in the zirconium raw material in the third heat treatment step is 0.1 to 5 mol parts per 100 mol parts of total metals excluding lithium in a mixture of the first and second semi-finished positive active materials.

17. A lithium secondary battery comprising a positive electrode containing the positive electrode active material for lithium secondary batteries according to any one of claims 1 to 10, a negative electrode, and an electrolyte.

Citation Information

Patent Citations

  • Nonaqueous electrolyte secondary battery cathode active material and manufacturing method thereof and secondary battery

    JP2013206679A

  • Nickel-based active material for lithium secondary battery, method of preparing the same, and lithium secondary battery including positive electrode including the same

    JP2020074264A

  • Positive electrode active material and lithium secondary battery including the same

    JP2022042478A

  • Method for manufacturing a positive electrode active material for a lithium secondary battery and positive electrode active material for a lithium secondary battery manufactured by said method

    JP2022529817A

  • Method for manufacturing electrode active material

    KR1020210112325A